STRATEGI INTEGRASI NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK PENGUATAN KARAKTER SISWA: STRATEGI INTEGRASI NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK PENGUATAN KARAKTER SISWA - Muafiq, Ahmad; Chusnul Muali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to comprehensively describe and analyze the strategies for integrating religious moderation values in Islamic Religious Education (PAI) learning to strengthen students' character. The research employs a qualitative approach with a case study design, conducted at MTs. Riyadus Sholihin Ketapang Kademangan, Probolinggo City, from January to May 2025. Data collection techniques include interviews, observation, and documentation, while data analysis follows the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The findings reveal that the integration of religious moderation values in PAI learning at MTs. Riyadus Sholihin is achieved through a strategic synergy between: (1) incorporating moderation values into classroom PAI instruction, (2) teachers serving as role models of moderate behavior, (3) routine religious activities that internalize principles of tolerance and unity, and (4) continuous monitoring of moderation in daily interactions.